Viral etiology among the elderly presenting acute respiratory infection during the influenza season - Watanabe, Aripuanã Sakurada Aranha; Carraro, Emerson; Candeias, João Manuelo Grisi [UNESP]; Donalísio, Maria Rita; Leal, Élcio; Granato, Celso Francisco Hernandes; Bellei, Nancy (FapUNIFESP (SciELO), 2011)
Introduction: Acute respiratory tract infections are the most common illness in all individuals. Rhinoviruses have been reported as the etiology of more than 50% of respiratory tract infections worldwide. Te study prospectively evaluated 47 elderly individuals from a group of 384 randomly assigned for acute respiratory viral infections (cold or fu) and assessed the occurrence of human rhinovirus (HRV), influenza A and B, respiratory syncytial virus and metapneumovirus (hMPV) in Botucatu, State of São Paulo, Brazil. Methods: Forty-nine nasal swabs collected from 47 elderly individuals following inclusion visits from 2002 to 2003 were tested by GenScan RT-PCR. HRV-positive samples were sequenced for phylogenetic analysis. Results: No sample was positive for influenza A/B or RSV. HRV was detected in 28.6% (14/47) and hMPV in 2% (1/47). Of 14 positive samples, 9 isolates were successfully sequenced, showing the follow group distribution: 6 group A, 1 group B and 2 group C HRVs. Conclusions: Te high incidence of HRV during the months of the influenza season requires further study regarding HRV infection impact on respiratory complications among this population. Infection caused by HRV is very frequent and may contribute to increasing the already high demand for healthcare during the influenza season.
Etiologia viral de infec?o respirat?ia aguda entre idosos, durante a temporada de gripe
Keywords: Elderly; Genescan RT-PCR; Human rhinovirus; Respiratory viruses; Reverse transcription polymerase chain reaction